Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1089/pop.2013.0041
|View full text |Cite
|
Sign up to set email alerts
|

Treating Pain in Addicted Patients: Recommendations from an Expert Panel

Abstract: Clinicians may face pragmatic, ethical, and legal issues when treating addicted patients. Equal pressures exist for clinicians to always address the health care needs of these patients in addition to their addiction. Although controversial, mainly because of the lack of evidence regarding their long-term efficacy, the use of opioids for the treatment of chronic pain management is widespread. Their use for pain management in the addicted population can present even more challenges, especially when evaluating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 59 publications
0
29
0
1
Order By: Relevance
“…Manipulacije se največkrat pojavljajo pri oceni pacientove bolečine, kjer pogosto prihaja do nasprotij med oceno medicinske sestre in zahtevami pacientov, odvisnih od prepovedanih drog, po analgetični terapiji (Neville & Roan, 2014). Dokazano je, da z zlorabo opioidov nastanejo poškodbe centra za zaznavo bolečine in da imajo zato uživalci opioidov pomembno znižan prag bolečine (Cheatle, Comer, Wunsch, Skoufalos, & Reddy, 2014). Tako lahko zaključimo, da gre pri pacientih za dejanske nevrofiziološke spremembe, ki se kažejo v tem, da lahko v primerjavi z zdravimi posamezniki izraziteje občutijo bolečino.…”
Section: Diskusijaunclassified
“…Manipulacije se največkrat pojavljajo pri oceni pacientove bolečine, kjer pogosto prihaja do nasprotij med oceno medicinske sestre in zahtevami pacientov, odvisnih od prepovedanih drog, po analgetični terapiji (Neville & Roan, 2014). Dokazano je, da z zlorabo opioidov nastanejo poškodbe centra za zaznavo bolečine in da imajo zato uživalci opioidov pomembno znižan prag bolečine (Cheatle, Comer, Wunsch, Skoufalos, & Reddy, 2014). Tako lahko zaključimo, da gre pri pacientih za dejanske nevrofiziološke spremembe, ki se kažejo v tem, da lahko v primerjavi z zdravimi posamezniki izraziteje občutijo bolečino.…”
Section: Diskusijaunclassified
“…Literature is sparse regarding guidelines on prescribing controlled medications to patients with suspected or confirmed illicit drug use. 20 Previous literature has identified that individuals with alcohol, marijuana, hallucinogen, cocaine, stimulant, heroin, and sedative use disorders, as well as those with nicotine dependence, had a higher prevalence of prescription opioid use disorders. 21 These individuals were also found to have used prescription opioids non-medically more often than those without substance use disorders, with an incidence rate ratio between 1.46 to 1.96.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%
“…3 Few providers have training to identify the problem of opioid addiction or to use appropriate screening and conduct difficult conversations with patients about addiction and therapy options. [4][5][6] Moreover, in the primary care setting, medication assisted therapy (MAT) is underutilized. 7 Curricula to portray the application of interviewing techniques to approach patients with OUD is imperative to prepare future providers on how to evaluate opioid misuse, addiction, and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%